Desenvolvimento de plataforma de acionamento digital para motor a relutância variável 8/6 - Moraes Filho, Marcos José de (2017)
This work contributes to the study of the switched reluctance machine driven as motor, through the proposal of a drive system by current control. The main objective is to implement a modular system, allowing physical structure changes in a simplified mode, with robust components to support the imposed tests. The platform should provide data acquisition with precision and reliability, as well as providing security for the people and equipment during the tests performed. In order to achieve the main objective, some intermediate steps will be exposed and discussed, such as a brief approach to the operating principle of the switched reluctance machine; the presentation of the prototype used and the mechanical and electrical characteristics; definition of the system (converter) and computational simulation of switched reluctance motor 8/6 drive. The results obtained in the computational simulation will be discussed and compared with the experimental results. The validation of the proposed system is carried out by means of tests with known loads, verifying the current control act and the machine behavior for each of these tests.